Effect of fixation stitches on out-of-plane response of textile non-crimp fabric composites - Bhudolia, Somen Kumar (2020)
Non-crimp fabrics are fabric tapes stitched to an adjacent orthogonal fabric with no associated crimp. In the current research, the effect of fixation polyester stitches in improving through-the-thickness properties of non-crimp fabric composite laminates is investigated. Detailed experimental studies on interlaminar fracture toughness and static indentation properties of stitched and unstitched thin ply carbon fibre epoxy composites have been conducted. About 23% higher peak load and 37% higher energy absorption were noticed during static indentation tests for the stitched ply composites. A detailed SEM investigation has shown that the stitch-stitch interaction ‘within a bi-angle ply’ and ‘between the bi-angle ply’ plays a significant role in reducing the delamination extent. The critical energy release rate during Mode I fracture toughness of stitched composites was found to be 26.5% higher and SEM investigation depicted that the stitches promote the intra-laminar delamination and enhance the toughness of the composite.